The Role Of The Work Environment In Improving The Performance Of The Karawang DPRD Secretariat - Siti Maesaroh; Nandang; Zenita Apriani (Enrichment : Journal of Management, 2022)
The problem in this study is about the application of the work environment in improving the performance of the employees of the Karawang Regency DPRD Secretariat, where the purpose of this study is to determine and analyze the work environment in improving employee performance at the Karawang DPRD Secretariat. In answering these problems, researchers used qualitative research. The primary data in this article is from interviews with employees of the Karawang DPRD Secretariat, while the secondary data in this article comes from data on employee performance appraisal reports and employee promotion reports. In this study, the researcher used a purposive sampling technique, which consisted of key informants, main informants, and supporting informants. The results of the study of this article can be concluded that the work environment at the Karawang DPRD Secretariat is quite good,as seen from the employees who work optimally based on the good employee performance appraisal report and 9 (nine) employees who have been promoted.